2022
DOI: 10.1007/s12020-022-03211-8
|View full text |Cite|
|
Sign up to set email alerts
|

Residual risks of comorbidities after parathyroidectomy in a nationwide cohort of patients with primary hyperparathyroidism

Abstract: Purpose: Primary hyperparathyroidism (PHPT) is a common endocrine disorder with increasing incidence, while epidemiologic data in Asian population has been lacking. Therefore, we aimed to identify the incidence, prognosis, and prognostic factors of PHPT patients who underwent parathyroidectomy in Korea.Methods: In this retrospective nationwide cohort, patients with PHPT were de ned as those with diagnostic codes of PHPT and procedural codes for parathyroidectomy, excluding chronic renal failure or secondary hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…However, the authors pointed out an interesting trend: in cases where patients with hypertension underwent parathyroidectomy, there was a suggestion of reduced risk of major cerebrovascular events compared to the comparison subjects who did not undergo parathyroidectomy (hazard ratio of 0.87; 95% confidence interval: 0.75–1.01) ( 11 ). In conjunction with the study by Grant et al , we recently reported that patients who had parathyroidectomy with complications, notably mood disorders, faced heightened risks of cardiovascular and cerebrovascular events, as well as mortality ( 3 ). While both studies draw from nationally representative datasets, it is important to note a crucial distinction in the racial composition of the patient populations that our study included only Asians and the study by Grant et al included mostly Caucasians.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…However, the authors pointed out an interesting trend: in cases where patients with hypertension underwent parathyroidectomy, there was a suggestion of reduced risk of major cerebrovascular events compared to the comparison subjects who did not undergo parathyroidectomy (hazard ratio of 0.87; 95% confidence interval: 0.75–1.01) ( 11 ). In conjunction with the study by Grant et al , we recently reported that patients who had parathyroidectomy with complications, notably mood disorders, faced heightened risks of cardiovascular and cerebrovascular events, as well as mortality ( 3 ). While both studies draw from nationally representative datasets, it is important to note a crucial distinction in the racial composition of the patient populations that our study included only Asians and the study by Grant et al included mostly Caucasians.…”
mentioning
confidence: 83%
“…Primary hyperparathyroidism (PHPT) is an increasingly prevalent endocrine disorder, with an incidence ranging from 1.3 to 50 cases per 100,000 person-years according to previous reports ( 1 - 3 ). Characterized by the excessive secretion of parathyroid hormone and subsequent hypercalcemia, PHPT can show non-classical manifestation of cardiovascular and psychological systems as well as classical manifestation targeted the skeletal and renal systems ( 4 - 6 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2) a procedure code for parathyroidectomy (P4541, P4542, or P4543); and (3) a history of admission [78]. In a retrospective cohort study estimating the prevalence of nonsurgical hypoparathyroidism and the risk of complications, nonsurgical hypoparathyroidism was defined as the presence of the ICD-10 codes (D82.1, E20.0, E20.8, E20.9, E31.0, E31.8, or E31.9) and at least two prescriptions for active vitamin D analogs.…”
Section: Operational Definitions Of Parathyroid Disordersmentioning
confidence: 99%
“…Primary hyperparathyroidism (PHPT) is a common endocrine disorder with a globally increasing incidence [1,2]. It is the primary cause of outpatient hypercalcemia and presents with a wide spectrum of symptoms impacting the renal, skeletal, neurological, cardiovascular, and gastrointestinal systems [3].…”
Section: Introductionmentioning
confidence: 99%